Hydroxytyrosol Protects against Myocardial Ischemia/Reperfusion Injury through a PI3K/Akt-Dependent Mechanism - Pei, Ying-hao (Mediators Inflamm, 2016)
Objective. To investigate the effects and mechanisms of hydroxytyrosol (HT) during the pathogenesis of myocardial ischemia reperfusion (I/R) in rat hearts. Methods. The rats were randomized into five groups: sham group, I/R group, HT+I/R group, HT+LY294002+I/R group, and LY+I/R group. Myocardial infarct size, markers of oxidative stress, extent of myocardial apoptosis, echocardiographically assessed cardiac function, and expression of Akt and GSK 3β were measured in each group. Results. Prereperfusion administration of HT was associated with a significantly smaller area of myocardial infarction and remarkably decreased level of myocardial apoptosis and necrosis, as evidenced by a lower apoptotic index, reduced cleaved caspase-3, and the serum activities of lactate dehydrogenase and creatinine kinase MB. Moreover, HT also attenuated the impairment of cardiac systolic function. However, cotreatment with LY294002 and HT completely abolished the above cardioprotective effects of HT. A subsequent mechanistic study revealed that the cardioprotective effects of HT during the process of I/R of the myocardium were dependent on the activation of the Akt/GSK3β pathway. Conclusion. Pretreatment with HT may have antiapoptotic and cardioprotective effects against myocardial I/R injury, and these effects seem to be related to the activation of the Akt/GSK3β pathway in the myocardium.